Retrospective Analysis of Patient Presentations at the Sydney (Australia) Royal Easter Show from 2012 to 2014. Issue 2 (31st January 2017) - Crabtree, Nathan; Mo, Shirley; Ong, Leon; Jegathees, Thuvarahan; Wei, Daniel; Fahey, David; Liu, Jia (Jenny)
Abstract: Introduction: Comprehensive studies on the relationship between patient demographics and subsequent treatment and disposition at a single mass-gathering event are lacking. The Sydney Royal Easter Show (SRES; Sydney Olympic Park, New South Wales, Australia) is an annual, 14-day, agricultural mass-gathering event occurring around the Easter weekend, attracting more than 800, 000 patrons per year. In this study, patient records from the SRES were analyzed to examine relationships between weather, crowd size, day of week, and demographics on treatment and disposition. This information would help to predict factors affecting patient treatment and disposition to guide ongoing training of first responders and to evaluate the appropriateness of staffing skills mix at future events. Hypothesis: Patient demographics, environmental factors, and attendance would influence the nature and severity of presentations at the SRES, which would influence staffing requirements. Methods: A retrospective analysis of 4, 141 patient record forms was performed for patients who presented to St John Ambulance (Australian Capital Territory, Australia) at the SRES between 2012 and 2014 inclusive. Presentation type was classified using a previously published minimum data set. Data on weather and crowd size were obtained from the Australian Bureau of Meteorology (Melbourne, Victoria, Australia) and the SRES, respectively. Statistical analyses were performed using SPSS v22 (IBM; Armonk, New York USA). Results: Between 2012 to 2014, over 2.5 million people attended the SRES with 4, 141 patients treated onsite. As expected, the majority of presentations were injuries (49%) and illnesses (46%). Although patient demographics and presentation types did not change over time, the duration of treatment increased. A higher proportion of patients were discharged to hospital or home compared to the proportion of patients discharged back to the event. Patients from rural/regional locations (accounting for 15% of all patients) were more likely to require advanced treatment, health professional review, and were more likely to be discharged to hospital or home rather than discharged back to the event. Extremes of temperature were associated with a lower crowd size and higher patient presentation rate (PPR), but had no impact on transfer or referral rates to hospital. Conclusion: This study demonstrated that analyses of patient presentations at an agricultural show provide unique insights on weather, attendance, and demographic features that correlated with treatment and disposition. These data can help guide organizers with information on how to better staff and train health care providers at future mass-gathering events of this type. N Crabtree, S Mo, L Ong, T Jegathees, D Wei, D Fahey, J Liu .Retrospective analysis of patient presentations at the Sydney (Australia) Royal Easter Show from 2012 to 2014 .Prehosp Disaster Med .2017 ;32 (2 )187 –194 .